Atypical inflammation of the middle ear - Garov, E V; Kryukov, A I; Zelenkova, V N; Sidorina, N G; Kaloshina, A S (Vestnik otorinolaringologii, 2017)
The objective of the present study was to characterize the patients presenting with atypical inflammation of the middle ear and consider the currently available methods for their examination. A total of 20 patients at the age from 16 to 66 years were admitted to the Department of Ear Microsurgery during the period from 2008 and 2016 for the treatment of atypical inflammation of the middle ear. Eleven of them (18 ears) were found to have tuberculous lesions (TL) of the middle ear while the remaining 9 patients (11 ears) suffered giant cell vasculitis (GCV). All the patients underwent the general clinical and otorhinolaryngological examination, computed tomography of the temporal bones and the thoracic cavity organs, cytological, bacteriological, pathomorphological, and molecular-genetic studies including PCR diagnostics, rheumatological tests, as well as counseling by a phthisiotherapist and rheumatologist. The primary localization of TL in the middle ear was documented in 6 patients including its association with lung lesions in 5 cases. The clinical picture of the disease in 5 patients was that of smoldering exudative pathology and in 6 ones was accompanied by suppurative perforative otitis media. According to the laboratory analyses, bacteriological diagnostics proved efficient in 9% of the patients, pathomorphological and cytological diagnostics in 18% and 27.3% of the cases respectively while the effectiveness of PCR diagnostics was estimated at 55%. The diagnosis in individual patients was established within the period from 1 month to 1.5 years after they first sought medical advice in connection with complaints of the ear disease. Tuberculosis of the middle ear began to develop as exudative middle otitis that acquired the form of bilateral pathology in 4 patients. Three patients had a concomitant pulmonary disease. In 4 patuents, the diagnois of middle ear tuberculosis was established based on the presence of the specific antibodies and in 5 ones based on the results of the pathomorphological study. All the studies were carried out in duplicate. The period between the beginning of the disease and the establishment of the definitive diagnosis varied from 1 month to 1 year.